PENGARUH SELF EFFICACY, SENIORITAS AUDITOR DAN REWARD TERHADAP AUDIT JUDGMENT - Ni Luh Putu Listya Sari; I Made Endra Lesmana Putra (UNHI Press, 2021)
This study was intended to test the effect of self-efficacy, auditor seniority and reward on audit judgment. This study collected main data using a questionnaire that was distributed directly to respondents. The subjects of this study were auditors who worked at KAP in Bali Province which were registered in the IAPI Directory in 2019. The sampling method used in this study was purposive sampling technique. 70 questionnaires have been distributed and 55 questionnaires can be used for further analysis. The analysis technique used in this research is multiple linear regression analysis. The conclusion in this study is that self-efficacy has a positive effect on audit judgment, auditor seniority has no significant effect on audit judgment and reward has a positive effect on audit judgment.